Ectopic Thyroid at the Base of the Tongue of a Young Patient - Paulo Henrique de Souza Castro; Luiz Evaristo Ricci Volpato; Julia Tramujas; Alvaro Henrique Borges (Case Reports in Dentistry)
Lingual thyroid is defined as an ectopic thyroid gland tissue located in the midline of the tongue base and it is uncommonly observed in clinical practice and is rare in children. This paper describes the surgical treatment of ectopic thyroid at the base of the tongue in a child. The chief complaint of the 12-year-old, melanodermic female patient was the difficulty to swallow for 15 days. The intraoral physical examination barely showed a nodular lesion at tongue base. The CT scan showed a round, well defined hyperdense lesion of approximately 25.8 mm at its largest diameter, with infiltrative growth in the posterior region of the base of the tongue. The proposed treatment was complete resection of the lesion. The histopathological diagnosis was lingual thyroid. After the diagnosis was established, the patient was referred to an endocrinologist for exams and medical follow-up. Lingual thyroid is a rare condition and its diagnosis in children is even rarer. Its approach should be transdisciplinary and should take into consideration the hormonal aspects of the patient in addition to the clinical condition of the lesion. In the presented case, the removal of the alteration was performed via conservative surgical procedure followed by immediate referral of the patient to the endocrinologist for a follow-up.